Pelatihan Manajemen Konflik Bagi Masyarakat - Saleh, Munandi (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2023)
Conflict management training for the community is one solution to the problems faced by RT and RW Cisaat Village, namely the lack of understanding related to disagreements related to the values of community harmony, good communication procedures in community life, emotional control, lack of conflict management skills, and cultural and different values in the community. The purpose of this activity is to increase understanding of RT and RW Cisaat Village related to managing conflicts well in the community. The method of implementing this activity is training for RT and RW Cisaat Village, Cisaat District, Sukabumi Regency. The partner in this training activity is the Cisaat Village Community Empowerment Institute. The evaluation was carried out by giving questionnaires to trainees before and after delivering the material, and as a result, the comprehension ability of the participants increased by 40.84%.